A multi-faceted, location-specific assessment of land degradation threats to peri-urban agriculture at a traditional grain base in northeastern China. (1st October 2020) - Li, Wenbo; Wang, Dongyan; Li, Yuefen; Zhu, Yuanli; Wang, Jingying; Ma, Jiamin
Abstract: Urbanization-induced cultivated land degradation can hamper the ability of peri-urban agriculture (PUA) to deliver clean food and agroecosystem services. Detailed geo-information about which cultivated lands are being influenced by urbanization will be important to designing future measures for the conservation of PUA. This information will be especially relevant for traditional grain bases because PUA is often underappreciated in these regions. For this reason, we performed a multi-faceted and location-specific assessment, including soil pollution, soil fertility, basic tillage conditions and land fragmentation, of cultivated land in a rural-urban transition zone outside of a city in northeast China. We also illustrated the combined risks in different urbanized environments via GIS-based two-step spatial clustering. The results indicated that, in general, cultivated lands were more polluted and fragmented, as well as less fertile and tillable, the closer they were to the urban area. Most of the affected cultivated lands were located within 8 km of the urban periphery. Furthermore, certain urban environments exposed the surrounding cultivated lands to specific degradation in relation to different combined risks. PUA in long-standing industrial areas mainly faced risks of polluted agricultural production, underutilization and impaired landscape ecological security (LES), whereas cultivated lands close to a recently developed residential area were characterized by risks of supplying service disruption, unsustainable agricultural production, underutilization and impaired LES. The present study highlighted that PUA associated with traditional grain bases must be preserved to enhance urban sustainability and resilience, and suggests that measures which can adapt to multi-faceted local degradation issues will be the most effective protection for peri-urban areas. Furthermore, the results also suggest that multi-functional and profitable agriculture will contribute to breaking the vicious circle of land degradation in peri-urban cultivated areas of traditional grain bases. Graphical abstract: Image 1 Highlights: A multi-faceted, location-based assessment of urban threats to farmland is presented. Urban lands were more polluted and fragmented, and less fertile, than rural lands. Certain urban environments caused specific combined risks to agriculture. The results supported adaptive protection measures for peri-urban cultivated lands. Farming in grain production areas should be restructured to be more multi-functional.